2022
DOI: 10.3390/jfmk7020043
|View full text |Cite
|
Sign up to set email alerts
|

Significantly Delayed Medium-Latency Response of the Stretch Reflex in Delayed-Onset Muscle Soreness of the Quadriceps Femoris Muscles Is Indicative of Sensory Neuronal Microdamage

Abstract: Unaccustomed or strenuous eccentric exercise is known to cause delayed-onset muscle soreness. A recent hypothesis postulated that mechano-energetic microinjury of the primary afferent sensory neuron terminals in the muscle spindles, namely a transient Piezo2 channelopathy, could be the critical cause of delayed-onset muscle soreness in the form of a bi-phasic non-contact injury mechanism. This theory includes that this microlesion could delay the medium-latency response of the stretch reflex. Our aim with this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(45 citation statements)
references
References 48 publications
1
34
0
Order By: Relevance
“…Furthermore, Alvarez et al and Bullinger et al showed permanent central synaptic disconnection of proprioceptors from motoneurons after nerve injury, and this phenomenon is associated with the loss of vesicular glutamate transporter (VGLUT) 1/Ia synapses on motoneurons [ 20 , 21 ]. Sonkodi et al suggested that the muscle spindle origin of increased M-wave latency on motoneurons after eccentric exercise-induced muscle damage should not be excluded [ 22 ] and even proposed that the transiently impaired muscle spindle-derived proprioceptors and the resultant synaptic disconnection on motoneurons are responsible for the increased M-wave latency in DOMS, in line with the findings of Vincent, Alvarez and Bullinger et al [ 19 , 20 , 21 , 22 ].…”
Section: Neural Microdamage Of Domsmentioning
confidence: 70%
See 3 more Smart Citations
“…Furthermore, Alvarez et al and Bullinger et al showed permanent central synaptic disconnection of proprioceptors from motoneurons after nerve injury, and this phenomenon is associated with the loss of vesicular glutamate transporter (VGLUT) 1/Ia synapses on motoneurons [ 20 , 21 ]. Sonkodi et al suggested that the muscle spindle origin of increased M-wave latency on motoneurons after eccentric exercise-induced muscle damage should not be excluded [ 22 ] and even proposed that the transiently impaired muscle spindle-derived proprioceptors and the resultant synaptic disconnection on motoneurons are responsible for the increased M-wave latency in DOMS, in line with the findings of Vincent, Alvarez and Bullinger et al [ 19 , 20 , 21 , 22 ].…”
Section: Neural Microdamage Of Domsmentioning
confidence: 70%
“…Finally, Alvarez et al showed that in the case of peripheral nerve injury, the VGLUT1 synapses of Type Ia central terminals are lost permanently on motoneurons, leading to a loss of proprioceptive feedback from the muscle spindles [ 21 ]. Sonkodi et al proposed a similar disruption, however acutely or transiently, in VGLUT1 transmission on motoneurons in DOMS when transient Piezo2 channelopathy is present [ 22 ]. As a result of the lost VGLUT1 synapses, the NMDA receptors at the axonal endings of the same pseudounipolar proprioceptive neurons could be activated, namely, at the presynaptic central terminal on the spinal dorsal horn [ 31 , 60 , 61 ].…”
Section: Transient Piezo2 Channelopathymentioning
confidence: 99%
See 2 more Smart Citations
“…The proprioceptive signalling of MSs and Golgi tendon organs (GTOs) is essential for the non-autonomous morphologic restoration of microfractured bones or remodelling [ 15 , 16 ]. Moreover, it is suggested that the primary transient proprioceptive terminal Piezo2 microinjury concomitant with microfractures impairs the static phase firing encoding of the stretch reflex [ 7 , 10 , 17 , 18 ] and correspondingly, this impairment could be realigned by the dynamic encoding of MSs and GTOs [ 19 , 20 ]. Hence, proprioceptive sensory neurons are proposed to have a role not only in the guidance of growth and regeneration, but also remodelling [ 6 , 9 , 10 ].…”
Section: Primary Non-contact Injury Phasementioning
confidence: 99%